Community Benefit Report Spending and Content Analysis - Swift, Orry; Colon, Ricardo (Journal of Applied Business and Economics, 2021)
There is substantial debate regarding the community benefits provided by nonprofit hospitals in exchange for tax-exempt status at the federal and state levels. Despite the controversy surrounding this topic, research into community benefit spending is a relatively new area of academic research. This study examines community benefit reports from nonprofit hospitals in the California Office of Statewide Health Planning and Development (OSHPD) database. We employ text-based content analysis to determine how the language used in current-year reports impacts community benefit spending in the following year. Our study contributes to the literature because it is the first paper that conducts text-based content analysis of community benefit reports using the following five textual characteristics: length, boilerplate, fog, specificity, and tone. We find that the length, specificity, and tone of the reports significantly impact community benefit spending.